U C Berkeley Co-op Friends Annual Heavy-Sacramento - Watkins, Howard::::::::: (1983)
Howard Watkins wearing suit with Fresno State T-shirt graciously accepting Buffoon Award; Cathy Barkett, Joe Barkett, Terri Mesple, Dale Mesple